208 Single Cell RNA Sequencing (Scrna-seq) in Studying the Early Embryonic Muscle Development. (21st September 2022) - Zhao, Liang; Du, Min
Abstract: During the early development, skeletal muscle, adipose, and connective tissues have high plasticity and are sensitive to in uterine nutritional fluctuations. During the past decade, maternal nutrition-induced changes in myogenesis and adipogenesis during the fetal stage have been extensively studied and their alterations are closely associated with changes in production efficiency and meat quality of farm animals. Organogenesis initiates during the embryonic stage, which sets the blueprint for later growth and development. Limited but growing evidence support that nutritional changes during the early embryonic stage also have profound effects on animal production efficiency. Using single-cell transcriptomic analysis (scRNA-seq), we investigated the effects of maternal obesity (MO) on the embryonic myogenesis in embryonic day 9.5 (E9.5) mouse embryos. First, we identified myogenic subpopulations within the dermomyotome (DM) and a developmental trajectory of embryonic myogenesis was reconstructed. Our results showed that MO induced systematic hypoxia, which was correlated with enhanced BMP signaling and impaired skeletal muscle differentiation within the DM. The Notch-signaling effectors, HES1 and HEY1, which act downstream of BMP signaling, were activated by hypoxia-inducible factor 1 (HIF1A) and suppressed myogenic differentiation through transcriptionally repressing an important myogenic regulator MEF2C. In conclusion, MO induces hypoxia and impairs myogenic differentiation by up-regulating BMP signaling within the DM, which may account for the disruptions of skeletal muscle development and function in progeny. Understanding the developmental programming of the skeletal muscle, as well as adipose and fibrotic tissues, especially at the embryonic stage, will facilitate the development of stage-specific nutritional management strategies to optimize production efficiency and meat quality.